ENHANCING MATHEMATICAL LITERACY THROUGH GEOGEBRA CLASSROOM-ASSISTED LEARNING: A CASE STUDY IN INDONESIAN SECONDARY SCHOOLS - Raisatunnisa; Suryadi, Didi; Fatimah, Siti; Priatna, Nanang; Nasir, Norma (MATEMATIKA DAN PEMBELAJARAN, 2025)
Mathematical literacy is important for helping students solve real-world problems through mathematical reasoning. However, students in Indonesia still demonstrate low performance in this area. This study aims to examine the effectiveness of GeoGebra Classroom-assisted learning in improving the mathematical literacy of eighth-grade students on the topic of exponents and roots. Using a qualitative descriptive method, data were collected from 22 students through written tests, questionnaires, and interviews. The results showed that GeoGebra Classroom supported conceptual understanding, improved visualization of abstract material, and increased student motivation and engagement. The use of this interactive technology had a positive impact on all indicators of mathematical literacy. These findings suggest that GeoGebra Classroom is an effective tool for enhancing mathematical literacy, and further research with larger and more diverse samples is recommended to strengthen and expand upon these results.